Extraction and Determination of Nickel (Ii) Via Cloud Point Method - A.Wannas, Fatimah; K.Jawad, Shawket (International Journal of Engineering and Technology, 2018)
Spectrophotometric  study for ion pair complex of Ni(II) ion extracted into cloud point extraction larger appear wave length of maximum absorbance was λ=660 nm, for extracted Ni(II) ion as ion pair association ,used laboratory synthesized azo derivative 2-(4-hydroxy phenyl azo)-4-Benzen naphthol(HPAB).The study about Determination the optimum condition for extraction and  determination was pH  =10 in presence 100 µg Ni(II) in 10 ml aqueous solution ,0.6 mL of Triton x-114 and temperature of heating was 70 c° at heating time equal to 30 minute, stoichiometry shows the ion pair complex extracted was 1:1 (Ni-HPAB) +2;2Cl_, in addition to electrolyte effect study as well as spectrophotometric determination of Ni(II) in different samples .